INTERPRETASI KATA LOGOS DAN THEOS DALAM YOHANES 1:1 - Yusuf L. M. (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2020)
Logos is Theos has always been a topic of heated discussion among Christian theologians. This subject is also often misinterpreted so that interpretations emerge that are not biblical or not following their original meaning. Logos is often accused of originating from the concept of Greek philosophy because John is considered to be much influenced by the Hellenistic world. Logos is often interpreted in the context of John 1:1 only divine, a God, or inferior to God because grammatically, the phrase "the Word is God" is assumed to provide that understanding. This phrase becomes polemic because the word Theos in the text does not use the article that can confirm the word is the same as God. Although Theos grammatically does not use the article's clothing, logos cannot be interpreted as a God, or the Logos is only divine because the third ho logos in the phrase refers to the nominative subject so that the noos becomes the predicate nominative and the article clothing is usually omitted. So if interpreted logos, it is God. This is confirmed in the first and second phrases that the logos is a person who stands alone, has his existence since eternity. He existed before the work of creation, and He is the creator, and from eternity already exists with God. Thus to answer this polemic, this study seeks to explain the concept of logos used by John and explains logos is God in the context of John 1:1 by using an interpretive analysis of words, phrases, or clauses in the text to get the correct meaning in context the original.